Physical environments of water containers and Aedes sp larvae in dengue endemic areas of Tanjungpinang Timur District - Rinaldi Daswito; Kholilah Samosir (Berita Kedokteran Masyarakat (BKM), 2021)
Purpose: This study aimed to determine the relationship of the type and condition of the container environment to the existence of Aedes sp larvae in Tanjungpinang Timur District. Methods: An observational study with a cross-sectional approach involved 401 houses with containers in Tanjungpinang Timur District, Tanjungpinang City. Data on the existence of larvae was performed using the single larvae method. Data on container type and container environmental conditions (water pH, water temperature, air temperature, air humidity) and the presence of larvae were collected by observing and measuring. Results: 863 containers were observed, 138 of them (15.99%) were found larvae of Aedes sp, containers inside the house (65.57%), and not closed (88.53%). The types of containers were controllable sites (95.13%), disposable sites (3.36%), and under controllable sites (1.51%). The results of the measurement of water pH (76.13%) and water temperature (82.73%) of the containers were categorized as good. Container temperature 98.38% showed results with a range of unfavorable conditions (<200C &> 300C) and air humidity of 99.07% with a range (<81.5% &> 89.5%). Type, location, condition of container closure, water pH, water temperature, and air temperature of containers were related to the presence of larvae in Tanjungpinang Timur District (p value <0.05), while the variable humidity was not related to the existence of larvae. Conclusion: Physical environmental factors strongly support the reproduction of DHF vectors in the East Tanjungpinang District. It is necessary to increase public knowledge and routine home eradication of mosquito nests (PSN), especially controllable site containers widely used as water reservoirs.